(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This scientific article is devoted to the study of the characteristics of professional stress among school teachers. Occupational stress is a significant problem in the educational field, and its study is important for ensuring the health and well-being of teachers, as well as the quality of education in general. The article discusses various aspects of stress, including its causes, consequences and management methods. Factors that contribute to stress among school teachers, such as curriculum overload, conflicts with students, and limited support from the administration, are also analyzed.